Oxalate Alters Cellular Bioenergetics, Redox Homeostasis, Antibacterial Response, and Immune Response in Macrophages - Kumar, Parveen; Saini, Kanchan; Saini, Vikram; Mitchell, Tanecia (Frontiers in Immunology, 2021)
Individuals with calcium oxalate (CaOx) kidney stones can have secondarily infected calculi which may play a role in the development of recurrent urinary tract infection (UTI). Uropathogenic Escherichia coli (UPEC) is the most common causative pathogen of UTIs. Macrophages play a critical role in host immune defense against bacterial infections. Our previous study demonstrated that oxalate, an important component of the most common type of kidney stone, impairs monocyte cellular bioenergetics and redox homeostasis. The objective of this study was to investigate whether oxalate compromises macrophage metabolism, redox status, anti-bacterial response, and immune response. Monocytes (THP-1, a human monocytic cell line) were exposed to sodium oxalate (soluble oxalate; 50 µM) for 48 hours prior to being differentiated into macrophages. Macrophages were subsequently exposed to calcium oxalate crystals (50 µM) for 48 hours followed by UPEC (MOI 1:2 or 1:5) for 2 hours. Peritoneal macrophages and bone marrow-derived macrophages from C57BL/6 mice were also exposed to oxalate. THP-1 macrophages treated with oxalate had decreased cellular bioenergetics, mitochondrial complex I and IV activity, and ATP levels compared to control cells. In addition, these cells had a significant increase in mitochondrial and total reactive oxygen species levels, mitochondrial gene expression, and pro-inflammatory cytokine (i.e. Interleukin-1β, IL-1β and Interleukin-6, IL-6) mRNA levels and secretion. In contrast, oxalate significantly decreased the mRNA levels and secretion of the anti-inflammatory cytokine, Interleukin-10 (IL-10). Further, oxalate increased the bacterial burden of primary macrophages. Our findings demonstrate that oxalate compromises macrophage metabolism, redox homeostasis, and cytokine signaling leading to a reduction in anti-bacterial response and increased infection. These data highlight a novel role of oxalate on macrophage function.